Comparison between CT Net enhancement and PET/CT SUV for N staging of gastric cancer: A case series. (September 2017) - Stabile Ianora, Amato Antonio; Telegrafo, Michele; Lucarelli, Nicola Maria; Lorusso, Valentina; Scardapane, Arnaldo; Niccoli Asabella, Artor; Moschetta, Marco
Abstract: Background: The therapeutic approach of gastric cancer strictly depends on TNM staging mainly provided by CT and PET/CT. However, the lymph node size criterion as detected by MDCT causes a poor differential diagnosis between reactive and metastatic enlarged lymph nodes with low specificity values. Our study aims to compare 320-row CT Net enhancement and fluorine-18 fluoro-2-deoxy-d -glucose positron emission tomography/computed tomography (F-FDG PET/CT) SUV for N staging of gastric cancer. Materials and methods: 45 patients with histologically proven gastric cancer underwent CT and F-FDG PET/CT. Two radiologists in consensus evaluated all images and calculated the CT Net enhancement and F-FDG PET/CT SUV for N staging, having the histological findings as the reference standard. CT and F-FDG PET/CT sensitivity, specificity, diagnostic accuracy, positive and negative predictive values (PPV and NPV) were evaluated and compared by using the Mc Nemar test. Results: The histological examination revealed nodal metastases in 29/45 cases (64%). CT Net enhancement obtained sensitivity, specificity, accuracy, PPV and NPV of 90%, 81%, 87%, 90% and 81%, respectively. F-FDG PET/CT SUV obtained sensitivity, specificity, accuracy, PPV and NPV of 66%, 88%, 73%, 90% and 58%, respectively. No statistically significant difference between the two imaging modalities was found (p = 0.1). Conclusion: CT Net enhancement represents an accurate tool for N staging of gastric cancer and could be considered as the CT corresponding quantitative parameter of F-FDG PET/CT SUV. It could be applied in the clinical practice for differentiating reactive lymph nodes from metastatic ones improving accuracy and specificity of CT. Highlights: Gastric cancer N staging represents a diagnostic challenge for patient management. CT and PET-TC play a crucial role in this field. CT has a high sensitivity and a low specificity. Disease over-staging causes ineffective care when patient categorized as palliative is excluded from curative treatment. The proposed new 3D CT software with quantitative data for N staging improves CT specificity.